2015
DOI: 10.1371/journal.pone.0144306
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Properties of Silver Nanoparticles in Bacillus subtilis Are Mediated by Released Ag+ Ions

Abstract: The superior antimicrobial properties of silver nanoparticles (Ag NPs) are well-documented, but the exact mechanisms underlying Ag-NP microbial toxicity remain the subject of intense debate. Here, we show that Ag-NP concentrations as low as 10 ppm exert significant toxicity against Bacillus subtilis, a beneficial bacterium ubiquitous in the soil. Growth arrest and chromosomal DNA degradation were observed, and flow cytometric quantification of propidium iodide (PI) staining also revealed that Ag-NP concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
115
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(136 citation statements)
references
References 60 publications
(65 reference statements)
8
115
1
3
Order By: Relevance
“…Several researchers have investigated the effects of AgNPs on the bacterial wall and how AgNPs inhibit bacterial growth [11, 12, and 13]. However, despite these studies, the exact mechanism underlying the anti-inflammatory effect of AgNPs is not clearly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have investigated the effects of AgNPs on the bacterial wall and how AgNPs inhibit bacterial growth [11, 12, and 13]. However, despite these studies, the exact mechanism underlying the anti-inflammatory effect of AgNPs is not clearly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Hsueh et al reported that a concentration of 10 ppm of Ag NPs exerts significant toxicity against B. subtilis, causing chromosomal DNA (deoxyribonucleic acid) degradation [55].…”
Section: Collagen-silver (Ag) Nps Compositesmentioning
confidence: 99%
“…Previously, heavy metal ions including silver ions were used for their microbial toxicity via reduction of the metal ions or formation of metal sulfides [12]. After the development in AgNPs production, the nanoparticles were used instead of the metal ion owing to their powerful toxicity effect [10,13,14]. The increase in the use of AgNPs in different sectors raised a concern due to their occasional release the environment [9].…”
Section: Introductionmentioning
confidence: 99%
“…Lots of studies proven that AgNPs penetrate different living cells [13,14]. Therefore, the action of those NPs is inside the cells and not at cellular surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation